Animal models for plaque rupture: a biomechanical assessment - Heiden, Kim Van der; Hoogendoorn, Ayla; Daemen, Mat J.; Gijsen, Frank J. H. (Thrombosis and Haemostasis, 2016)
Rupture of atherosclerotic plaques is the main cause of acute cardiovascular events. Animal models of plaque rupture are rare but essential for testing new imaging modalities to enable diagnosis of the patient at risk. Moreover, they enable the design of new treatment strategies to prevent plaque rupture. Several animal models for the study of atherosclerosis are available. Plaque rupture in these models only occurs following severe surgical or pharmaceutical intervention. In the process of plaque rupture, composition, biology and mechanics each play a role, but the latter has been disregarded in many animal studies. The biomechanical environment for atherosclerotic plaques is comprised of two parts, the pressure-induced stress distribution, mainly - but not exclusively – influenced by plaque composition, and the strength distribution throughout the plaque, largely determined by the inflammatory state. This environment differs considerably between humans and most animals, resulting in suboptimal conditions for plaque rupture. In this review we describe the role of the biomechanical environment in plaque rupture and assess this environment in animal models that present with plaque rupture.
Keywords: Animal models; atherosclerosis; biomechanics; devices